2013
DOI: 10.1002/ijc.28539
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop between STAT3 and cyclooxygenase‐2 gene may contribute to Helicobacter pylori‐associated human gastric tumorigenesis

Abstract: Persistent infection with Helicobacter pylori (H. pylori) contributes to gastric diseases including chronic gastritis and gastric cancer. However, the pathogenesis of this carcinogenic bacterium has not been completely elucidated. Here, we report that H. pylori rapidly triggers STAT3 signaling and induces STAT3-dependent COX-2 expression both in vitro and in vivo. STAT3 upregulats COX-2 by binding to and increasing the activity of COX-2 promoter. COX-2 in turn regulates IL-6=STAT3 signaling under basal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…This is consistent with other evidence that most cancers are predominantly related to environmental causes rather than hereditary, although the two factors interact (Polk and Peek, 2010;Rugge et al, 2013;Uehara et al, 2013). Cancer is the second most common cause of mortality in the western world after cardiovascular disease (Xiong et al, 2014;Assumpção et al, 2015).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with other evidence that most cancers are predominantly related to environmental causes rather than hereditary, although the two factors interact (Polk and Peek, 2010;Rugge et al, 2013;Uehara et al, 2013). Cancer is the second most common cause of mortality in the western world after cardiovascular disease (Xiong et al, 2014;Assumpção et al, 2015).…”
Section: Introductionsupporting
confidence: 78%
“…Some tumors with benign nomenclature are obviously malignant, for example; lymphoma, myeloma. Problems of classifying neuroendocrine tumors with diverse tissues of origin exists (Polk and Peek, 2010;Xiong et al, 2014). There exist also tumors of mixed cell phenotype which have posed a problem of histological classification, for example; tumors of salivary glands, teratomata also called "Monsters" (Irrazábal et al, 2014;Assumpção et al, 2015).…”
Section: Classification Of Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of STAT3 mutant in which tyrosine 705 is replaced by phenylalanine impairs tyrosine phosphorylation, nuclear translocation and the transcriptional activity in IL‐6‐stimulated cells . Moreover, H. pylori ‐positive gastritis tissues exhibited markedly higher levels of phosphorylation at the tyrosine residue 705 (P‐STAT3 Tyr705 ) than H. pylori ‐negative ones . However, roles for STAT3 in H. pylori ‐associated gastric carcinogenesis and underlying molecular mechanisms remain largely unveiled.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (49) observed that COX-2/prostaglandin E2 regulated JAK2/STAT3 signaling in colorectal cancer cells (49). Furthermore, Xiong et al (50) revealed that there is a positive feedback loop between the STAT3 and COX-2 genes that may contribute to Helicobacter pylori-associated human gastric tumorigenesis (50). However, the exact association The signal transducer and activator of transcription 3-cyclooxygenase-2 signaling pathway serves a function in the NaHS-induced production of VEGF in PLC/PRF/5 cells.…”
Section: The Stat3-cox-2 Signaling Pathway Participates In Nahs-inducmentioning
confidence: 99%